Understanding Generation Z through collective consciousness: Impacts for hospitality work and employment - Malinvisa Sakdiyakorn (2022)
This paper offers insights into Generation Z (Gen Z), using the collective consciousness as an underlying mechanism that shapes generationally distinct human values and behaviors. Written life narratives of 125 Gen Z, University students in Thailand, were used to identify links and commonalities between shared experiences, human values and work behaviors. A combination of major national and global events, personal events, social and technological vehicles played a key role in shaping Gen Z's collective consciousness, leading to a number of salient human values, including universalism, benevolence, self-direction, achievement and security. The links between collective consciousness and values offer a pathway to a more accurate understanding about generational groups and their corresponding work behaviors. Implications for managers and policy are offered which can facilitate attraction, retention and engagement of Gen Z in the 2020s workplace. Impacts of COVID-19 are addressed and suggestions offered in relation to potential impacts on this generation in a work context.